2018
DOI: 10.1002/cphc.201801063
|View full text |Cite
|
Sign up to set email alerts
|

A Robust and Cost‐Efficient Scheme for Accurate Conformational Energies of Organic Molecules

Abstract: Several standard semiempirical methods as well as the MMFF94 force field approximation have been tested in reproducing 8 DLPNO‐CCSD(T)/cc‐pVTZ level conformational energies and spatial structures for 37 organic molecules representing pharmaceuticals, drugs, catalysts, synthetic precursors, industry‐related chemicals (37conf8 database). All contemporary semiempirical methods surpass their standard counterparts resulting in more reliable conformational energies and spatial structures, even though at significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 98 publications
1
40
0
1
Order By: Relevance
“…45,65,66 Since some molecules in the original test set included iodine and some DLPNO-CCSD(T) By considering a large number of diverse organic molecules with many poses per molecule, we seek to sample a wide variety of conformer energy preferences (e.g., intramolecular hydrogen and halogen bonding, -stacking, electrostatic interactions, etc.). While using optimized low-energy conformers may under-estimate the accuracy of methods for high-energy struc-tures, 7 we believe the current work is a challenging but useful comparison. In general, such high-energy geometries reflect steric repulsion more than the diverse types of interactions driving low-energy geometries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…45,65,66 Since some molecules in the original test set included iodine and some DLPNO-CCSD(T) By considering a large number of diverse organic molecules with many poses per molecule, we seek to sample a wide variety of conformer energy preferences (e.g., intramolecular hydrogen and halogen bonding, -stacking, electrostatic interactions, etc.). While using optimized low-energy conformers may under-estimate the accuracy of methods for high-energy struc-tures, 7 we believe the current work is a challenging but useful comparison. In general, such high-energy geometries reflect steric repulsion more than the diverse types of interactions driving low-energy geometries.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work have suggested that the low correlations found between force field and semiempirical methods are derived from the small number of low-energy conformers considered in this benchmark. 7 Certainly, one might imagine that when considering multiple geometries with only small differences in energies, random errors are magnified. Figure 5 illustrates Despite the small ranges in energies, there is little correlation between the energy range of a molecule and the accuracy metrics of a particular method.…”
Section: Effects Of Conformer Energy Ranges On Accuracy Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conformational sampling with fast semi-empirical methods has seen tremendous development recently. [57][58][59][60] Combining them with DFT post-treatment allows, e.g., estimation of realistic IR spectra in solution 61 and reliable exhaustive conformational sampling of organic macrocycles. 62 Given the importance of CaC 2 as a sustainable carbon source for organic synthesis and Ca acetylides as potent intermediates, we performed this computational study.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Multiple efforts have evaluated the success of wavefunction and density functional first-principles methods to compare the energetics of different conformers. [6], [7], [8], [9], [10], [11], [12] While experimental crystal structures and bioactive docked conformers are not always the lowest energy conformer, recent efforts have demonstrated only small energy differences when using quantum chemical methods instead of force fields. [13], [14] Even for simple molecules such as 1,1'-biphenyl, use of large basis set coupled cluster methods are needed to accurately place the dihedral angle and barrier.…”
Section: Time (S) Introductionmentioning
confidence: 99%